2022
DOI: 10.1021/acs.inorgchem.2c03601
|View full text |Cite
|
Sign up to set email alerts
|

High Retention Immobilization of Iodine in B–Bi–Zn Oxide Glass Using Bi2O3 as a Stabilizer under a N2 Atmosphere

Abstract: The immobilization of iodine waste suffers from serious iodine loss during heat treatment. Herein, we reported on the high iodine retention immobilization of simulated radioiodinecontaminated Bi 0 −SiO 2 sorbent in B−Bi−Zn oxide glass using Bi 2 O 3 as a stabilizer under a N 2 atmosphere. The effects of the Bi 2 O 3 content and sintering atmosphere on the iodine immobilization behaviors (iodine retention ratio, phase composition, microstructure, and chemical stability) were investigated. It was found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Taylor and Lopata studied the hydrolytic stability of bismuth iodine compounds under various conditions and concluded that bismuth oxyiodides, such as Bi 5 O 7 I and BiOI, were excellent candidate waste forms for 129 I immobilization owing to their high chemical stability and low solubility in aqueous media. However, BiI 3 is not a suitable waste form for long-term storage and disposal because of its high susceptibility to hydrolysis and low thermal resistance. …”
Section: Introductionmentioning
confidence: 99%
“…Taylor and Lopata studied the hydrolytic stability of bismuth iodine compounds under various conditions and concluded that bismuth oxyiodides, such as Bi 5 O 7 I and BiOI, were excellent candidate waste forms for 129 I immobilization owing to their high chemical stability and low solubility in aqueous media. However, BiI 3 is not a suitable waste form for long-term storage and disposal because of its high susceptibility to hydrolysis and low thermal resistance. …”
Section: Introductionmentioning
confidence: 99%
“…Recent focus has converged on bismuth-based functional materials (BBMs) due to their significant advantages such as relatively high I 2 sorption capacity and low production costs. [26][27][28][29][30][31][32][33][34] Since Yang and coworkers reported the first BBM for efficient capture of radioactive iodine in 2015, [58,59] researchers have conducted a large amount of work in this field. However, there are still several issues regarding such materials that need to be addressed.…”
Section: Introductionmentioning
confidence: 99%